(untitled) (قضايا سياسية, 2024)
This study analyzes the Balancing strategies of intermediate (secondary and small) countries in international relations. It discusses in detail the Hedging Balancing and Balancing of Threat. It analyzes the Balancing motives and its external elements.It analytically reviews the types of Balancing. The study then discusses Balancing as a foreign policy for medium and small powers in the international system. The study then reviews the most prominent alternative strategies to balancing, which are Bandwagoning, Bonding, Binding, and Beleaguering, Hiding. This is done by testing three research hypotheses, the first is that balancing is a state's foreign policy that aims to equalize (power or threat) towards the most powerful states, and thus that state becomes less likely to dominate. This assumption is complemented by two other assumptions, which are that the Balancing theory is part of the balance of power theory, but a group of theoretical and applied differences makes them distinct. The second partial hypothesis is that positive Balancing aims to enhance the state's capabilities and consolidate its position in the international community, while negative Balancing strategy seeks to undermine the opponent's influence and reduce his capabilities. The study reached research results, the most important of which is that balancing is a policy or behavior that aims to try to match, exceed, or prevent the power of a stronger state from dominating the state. Through: an alliance to confront the hegemonic state, provided that the Balancing here is proactive. The balance can also be internal, as the state builds its own capabilities, whether military or the socio-economic base on which it depends. The internal balance is clearer when the growth rate exceeds the rate of growth of other countries, especially in military power, and then the country balances out all the stronger powers by catching up with them.